Efficacy of Benzoxazinorifamycins in a Mouse Model of Chlamydia pneumoniae Lung Infection - Campbell, Lee Ann (American Society for Microbiology (ASM), 2008)
The efficacy of rifalazil and other benzoxazinorifamycins was tested in a mouse model of lung infection against Chlamydia pneumoniae. Rifalazil and six related new chemical entities all showed efficacy after one dose per day for 3 days at either 3 or 1 mg/kg of body weight.